2013
DOI: 10.1002/er.3138
|View full text |Cite
|
Sign up to set email alerts
|

Exergetic analysis and economic evaluation of central tower receiver solar thermal power plant

Abstract: SUMMARY This article presents the analytical evaluation of a central tower receiver solar thermal power plant with air‐cooled volumetric receiver using exergy analysis. The energetic and exergetic losses as well as the efficiencies of a typical central tower receiver‐based solar thermal power plant have been carried out under the specific operating conditions. The enhancement in efficiency of the plant from the variation in power input to constant power input achieved by thermal storage backup condition has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Also there are heat transfer losses in the receiver due to convection, conduction and radiation. Heat losses can be expressed as [33,34]:…”
Section: Solar Subsystem Modelmentioning
confidence: 99%
“…Also there are heat transfer losses in the receiver due to convection, conduction and radiation. Heat losses can be expressed as [33,34]:…”
Section: Solar Subsystem Modelmentioning
confidence: 99%
“…It was found that the overall exergy and energy efficiencies of the plant can be increased to some extent by integrating advanced power cycles including supercritical Rankine cycles and reheat Rankine cycles. In a study by Reddy et al [48], evaluation of a solar tower power plant was performed using exergy analysis. The solar tower was integrated with a Rankine cycles for their study.…”
Section: Recent Advances In Renewable Energy Researchmentioning
confidence: 99%
“…Due to the exclusive conceptual characteristics of the exergy analysis, such methodology has been largely applied to analyze and optimize several energy systems such as thermoelectrical plants [7], vapor compression refrigeration systems [23], distillation columns [30], multicrystalline solar photovoltaic systems [18], supercritical thermoelectric coal plants assisted by solar concentrator [23], active solar distillation systems integrated with solar ponds [22], cogeneration with LNG [11] and desalination plants [9].…”
Section: Introductionmentioning
confidence: 99%